2019
DOI: 10.1111/imb.12576
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenin domain‐containing NlChP38 is necessary for normal ovulation in the brown planthopper

Abstract: The brown planthopper (BPH), Nilaparvata lugens, is a major threat to rice production. The eggshell plays an important role in insect reproduction. The constituents and formation process of BPH eggshells remains largely unknown. Here, we report a novel eggshell‐associated protein, NlChP38, containing an amelogenin domain, that is essential for normal ovulation in the BPH. NlChP38 is specifically expressed in the follicular cells from egg chambers at both RNA and protein levels. RNA interference of NlChP38 resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
6
0
4
Order By: Relevance
“…In Hemipteran insects, such as Cixius nervosus (Cixiidae) and Javesella pellucida , Conomelus anceps , N. lugens (Delphacidae), the developing oocytes are surrounded by a single layer of follicular cells. At the start of vitellogenesis, each follicular cell generates two nuclei, with the two nuclei positioned one on top of the other in the long axis of each cell [16,51]. Knockdown of NlRpn s disrupted the arrangement of follicular cells surrounding the oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Hemipteran insects, such as Cixius nervosus (Cixiidae) and Javesella pellucida , Conomelus anceps , N. lugens (Delphacidae), the developing oocytes are surrounded by a single layer of follicular cells. At the start of vitellogenesis, each follicular cell generates two nuclei, with the two nuclei positioned one on top of the other in the long axis of each cell [16,51]. Knockdown of NlRpn s disrupted the arrangement of follicular cells surrounding the oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4.9. Functional analysis of NlRpn and NlRac genes during ovulation and egg hatching Ovulation and egg hatching experiments were conducted according to Lou et al [16]. Briefly, newly emerged females were microinjected with each dsNlRpn or dsNlRac and royalsocietypublishing.org/journal/rsob Open Biol.…”
Section: Measurement Of Triglycerides In Ovaries and Fat Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the molecular basis underlying BPH reproduction has attracted great interest. Facilitated by the assembled genome of the BPH and RNA interference (RNAi)‐mediated gene function assay (Xu et al, 2013; J. Xue et al, 2014), a battery of genes were identified to be involved in the reproduction through affecting a series of reproduction‐associated events including oogenesis (Lu et al, 2018; N. Xu et al, 2019; Zhang et al, 2018), egg hatchability (Cheng et al, 2020; Shen et al, 2019), ovulation (Wu et al, 2017; Lou, Lu et al, 2019), egg transportation (Lou, Shen et al, 2019; Shen et al, 2021), and ovipositor development (K. L. Li et al, 2018; Mao et al, 2019; Zhang et al, 2018). These findings shed important insights into our understanding of BPH reproduction at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…In N. lugens , some progress has been made in understanding its reproductive regulation mechanisms. A mucin-like gene and an eggshell-associated NlChP38 gene, specifically expressed in the follicular cells, are essential for N. lugens oviposition [ 5 , 6 ]. We speculate that there are functional candidate genes contributing to oviposition success, but which remain unexplored.…”
Section: Introductionmentioning
confidence: 99%